INVESTIGATING NETWORK THREATS TO ENSURE MAXIMUM PROTECTION OF DATA AND INFRASTRUCTURE - LEMESHKO, ANDRIY; ANTONENKO АRTEM; KUVIK, NAZAR; HNIADYI, VLADYSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Networks are systems vulnerable to attackers because their main function is to facilitate remote access and data transfer. With the development of technology and the increase in the number of devices connected to networks, the number of potential network security threats is growing. This challenges information technology to continuously improve network security and reduce attack vulnerabilities. Information on networks must be safe and secure to enable efficient communication and data exchange on the network. Due to the challenges and threats to data in networks, network security is one of the most important aspects of an information technology infrastructure. Due to the fact that security is one of the main needs in information technology infrastructure, scientists have been conducting research in this area for many years. As a result, when building a network, network security measures are designed to reduce the ability of hackers to gain access to protected data. The goal of network security is to protect the network and its components from unauthorized access and abuse in order to provide users with safe and secure communications. This article provides an overview of recent developments in the field of network threats and security measures, as well as promising areas of research. The article discusses various network attacks and ways to improve the security of network data. Based on the analysis of recent research, this article discusses the main types and categories of network threats and attacks to which the network is exposed. Their classification is given and a detailed analysis of the features is carried out. Network security objectives can be provided in three categories: data confidentiality assurance, complete data maintenance, data availability maintenance. Much attention is paid to methods of protecting networks from unauthorized access and the impact of network threats. Based on a review of network security research, the article provides a list of effective network security measures to prevent network intrusions. The article also notes the importance of timely detection and response to network threats in order to ensure a high level of data transmission security on the network. The development and application of effective protection methods is a critical element in ensuring the security of networks and their users. Thus, new ideas in network security systems can be presented through the analysis of published works for further research.